Cardiac Fibroblasts Aggravate Viral Myocarditis: Cell Specific Coxsackievirus B3 Replication - Lindner, Diana; Li, Jia; Savvatis, Konstantinos; Klingel, Karin; Blankenberg, Stefan; Tschöpe, Carsten; Westermann, Dirk (Mediators of Inflammation, 2014)
Myocarditis is an inflammatory disease caused by viral infection. Different subpopulations of leukocytes enter the cardiac tissue and lead to severe cardiac inflammation associated with myocyte loss and remodeling. Here, we study possible cell sources for viral replication using three compartments of the heart: fibroblasts, cardiomyocytes, and macrophages. We infected C57BL/6j mice with Coxsackievirus B3 (CVB3) and detected increased gene expression of anti-inflammatory and antiviral cytokines in the heart. Subsequently, we infected cardiac fibroblasts, cardiomyocytes, and macrophages with CVB3. Due to viral infection, the expression of TNF-α, IL-6, MCP-1, and IFN-β was significantly increased in cardiac fibroblasts compared to cardiomyocytes or macrophages. We found that in addition to cardiomyocytes cardiac fibroblasts were infected by CVB3 and displayed a higher virus replication (132-fold increase) compared to cardiomyocytes (14-fold increase) between 6 and 24 hours after infection. At higher virus concentrations, macrophages are able to reduce the viral copy number. At low virus concentration a persistent virus infection was determined. Therefore, we suggest that cardiac fibroblasts play an important role in the pathology of CVB3-induced myocarditis and are another important contributor of virus replication aggravating myocarditis.